A beginner's guide to kintsugi : the Japanese art of repairing pottery and glass - Hori, Michihiro, 1975- (Tuttle Publishing, 2022)
The thought of throwing away a cherished dish or mug can be heartbreaking. If you've ever wanted to repair a treasured piece rather than tossing it in the trash--but didn't know how--the traditional Japanese art of Kintsugi ("gold repair") offers the perfect solution! --Amazon.com.